Motivasi Peserta Didik dalam Pembelajaran Daring pada Masa Pandemi Covid-19 di Sekolah Menegah Kejuruan - Muhammad Bayu; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2021)
Online learning has become a demand in the world of education since the last few years, especially during the current Covid-19 era. Online learning is carried out at home at all levels of education. This causes students to experience stress and become bored due to several obstacles that may occur in the habit of learning. This study aims to describe the motivation of students in using online learning systems during the Covid-19 pandemic at SMK Muhammadiyah 1 Padang. This type of research is descriptive research. This study tries to provide a systematic description of the facts and true nature of a particular population. This study uses quantitative research methods. The research instrument used in this study was a questionnaire distributed via google form which had 1 variable with 6 indicators. This questionnaire was tested first to students to find out the validity and reliability of this instrument. This research questionnaire was conducted in class XII TITL with a total of 17 respondents and the results obtained 9 respondents with moderate motivation results. It can be concluded that the motivation of students in online learning during the COVID-19 pandemic is categorized as moderate.